Acute Toxicity of Jatropha Curcas L. Latex and Its Histopathological Effects on Dental Pulp and Periapical Tissues - Fazwishni Siregar; Rini Damayanti (Faculty of Pharmacy, Universitas Gadjah Mada, 2020)
Traditional uses of Jatropha curcas L. latex,among others, are to cure toothache. This study aimed to evaluate the acute toxicity of J. curcas latex by oral route and to assess the histopathological effects of J. curcas latex on dental pulp and periapical tissues. For acute toxicity, the latex of 5 g/kg BW was administered intragastrically to the test groups of albino mice and water to the control groups. The assessment was based upon mortality, sign of toxicity, body weight, and histological evaluation of organs. Results showed no mortality in mice up to 5 g/kg body weight, no sign of toxicity, and no tissue alterations macroscopically and histopathologically were observed. There’s no significant difference in body weight between the test and control, both in male and female groups. For testing histopathologic effect on dental pulp, the latex was brought in contact with dental pulp and sealed. The assessment was based on the presence of inflammation and necrosis in dental pulp and periapical tissues, histopathologically. Results showed inflammation and necrosis, which was in direct contact with the latex were observed in a limited area, while underneath was normal pulp. No inflammation or necrosis in periapical tissues was observed in all groups. It caused coagulative necrosis in the pulp which was in direct contact with latex. It can be concluded that J. curcas latex is slightly toxic to mice at a single dose of oral administration. Inflammation and necrosis are observed on dental pulp which is in contact with latex while the tissue underneath is normal. It did not caused inflammation on periapical tissues.